Analisis Perkembangan Industri Game di Indonesia Melalui Pendekatan Rantai Nilai Global (Global Value Chain) - Abdurrahman Mulachela; Khairur Rizki; Y. A. Wahyuddin (The Department of International Relations Universitas Mataram, 2020)
This study aims to analyze how the impact of the development of the Indonesian gaming industry on the Indonesian economy. This study uses the concept of a global value chain as a tool to analyze the causes of market conditions, the role of actors, the value chain and the distribution of profits of the gaming industry in Indonesia which is currently detrimental to the Indonesian state. The conclusion obtained from this study is that the condition of the Indonesian gaming industry which is currently detrimental to the country is due to local industry actors who are unable to compete with foreign actors in the domestic market of the Indonesian game industry.